Gambaran Manajemen Diri Remaja Dalam Menghafal Al-Qur'an Di Rumah Tahfizh Al-Haramain Banjarmasin - Kamila, Muna; Yulia Hairina; Shanty Komalasari (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2023)
Self-management is a series of activities that are regulated to manage oneself well so that one is able to archieve the live goals that have been set. Self-management is very important in a person’s process to achieve something he wants to realize, for example memorizing the Qur’an. You can imagine how a teenager balances his two responsibilities to achieve his goals and dreams of being a memorizer of the Qur’an and becoming a student who excels in school, both in terms of managing time, planning, implementing plans, and other. This research is a type descriptive qualitative research. The subjects of this study were selected by purposive sampling. Data collection techniques included interviews, observations and documentation. The research subjects were early teenage students who memorized the Qur’an at Tahfizh Al-Haramain Banjarmasin’s house as well as being active students in school. Data analysis techniques were carried out in three stages, namely data reduction, data display, and draw conclusions. The results of the study show that there are similarities regarding adolescent self-management which includes four aspects, while in the factors affecting self-management found differences and similarities but there are differences in how to perform activity factors that affect self-management.